2015
DOI: 10.4081/ejh.2015.2546
|View full text |Cite
|
Sign up to set email alerts
|

Glycol methacrylate embedding for the histochemical study of the gastrointestinal tract of dogs naturally infected with Leishmania infantum

Abstract: In canine visceral leishmaniasis a diffuse chronic inflammatory exudate and an intense parasite load throughout the gastrointestinal tract (GIT) has been previously reported. However, these studies did not allow a properly description of canine cellular morphology details. The aim of our study was to better characterize these cells in carrying out a qualitative and quantitative histological study in the gastrointestinal tract of dogs naturally infected with Leishmania infantum by examining gut tissues embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Analysis of Th1, Th2, and Th17 cytokine responses by cultured peripheral blood mononuclear cells from patients who had developed kala-azar caused by Leishmania donovani , or who were protected against kala-azar, showed that IL-17 and IL-22 are the cytokines most strongly associated with protection against kala-azar (70). It has been reported that higher numbers of plasma cells, lymphocytes, and Mφ but lower number of MCs are present in the lamina propria of gastrointestinal tract of dogs naturally infected with L. infantum compared to non-infected controls, in all gastrointestinal tract segments (31). Thus, MCs may play different roles in visceral leishmaniasis and cutaneous leishmaniasis.…”
Section: Mcs In Leishmania Spp Infectionmentioning
confidence: 99%
“…Analysis of Th1, Th2, and Th17 cytokine responses by cultured peripheral blood mononuclear cells from patients who had developed kala-azar caused by Leishmania donovani , or who were protected against kala-azar, showed that IL-17 and IL-22 are the cytokines most strongly associated with protection against kala-azar (70). It has been reported that higher numbers of plasma cells, lymphocytes, and Mφ but lower number of MCs are present in the lamina propria of gastrointestinal tract of dogs naturally infected with L. infantum compared to non-infected controls, in all gastrointestinal tract segments (31). Thus, MCs may play different roles in visceral leishmaniasis and cutaneous leishmaniasis.…”
Section: Mcs In Leishmania Spp Infectionmentioning
confidence: 99%